1981
DOI: 10.1111/j.1151-2916.1981.tb15886.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of SrTiO3 Boundary‐Layer Capacitor Material

Abstract: SfliO, capacitor material with indiffused BiZ03 was studied using SEM, ESCA combined with Ar+ ion-etching, and TEM equipped with EDX. The apparent thickness of a second-phase layer observed with SEM was found to be influenced by in-depth effects. ESCA and TEM results show that only a 10-to 100-nm thick layer of second phase is present between the S f f i 0 3 grains. In addition, it was found with TEM that the outer part of each grain contained Bi (at most 2 at.%), representing a diffusion layer. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The total porosity, P, can be represented in terms of the number of grains and pores, n p , and their respective volumes, V g and V p , as Pϭ n P V P n g V g ϭ n P d P 3 n g d g 3 . ͑5͒…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total porosity, P, can be represented in terms of the number of grains and pores, n p , and their respective volumes, V g and V p , as Pϭ n P V P n g V g ϭ n P d P 3 n g d g 3 . ͑5͒…”
Section: Resultsmentioning
confidence: 99%
“…Such high charge-storage devices are made, for example, by diffusing a donor or acceptor dopant oxide into the grains of a semiconducting substrate material. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The explanation for the very high effective dielectric constants, eff , in IBLCs is not ascribed to large changes in the permittivity of the materials comprising the substrate. Rather, the enhancement is attributed to a change in the characteristic length scale associated with thin dielectric layers surrounding conducting cores of grains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping the observations and contradictions in view, we felt that it was important to synthesize phase pure STO doped with Mn. A survey of the earlier work demonstrates that SrTiO 3 could be prepared by various physical and chemical routes that include conventional solid-state reaction route, chemical-coprecipitation method, solgel, hydrothermal and electrochemical [20][21][22][23][24][25]. Bera et al [26] reported a simple technique for the formation of SrTiO 3 where the Strontium oxalate is precipitated over the fine TiO 2 particles (which facilitate seeding for heterogenous nucleation) followed by subsequent heat treatment at appropriate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Applying its semiconducting and dielectric properties by controlling the grain boundary, it is widely used for photoelectrodes 10,11 and devices of various boundarylayer capacitors. 12,13 For the rapidly progressing development of VLSI circuits, high purity ultrafine powders are required for manufacturing an electronic device of high capacity. 14 Recently, scientists took an interest in the sol-gel processes used to prepare high purity powders.…”
Section: Introductionmentioning
confidence: 99%